Fundamentals of instrumentation and measurement - Placko, Dominique; Wiley InterScience (Online service) (Newport Beach, CA ; London : ISTE Ltd., 2007)
'Instrumentation and Measurement' presents the general principles of instrumentation processes. The book explains the theoretical analysis of physical phenomena used by standard sensors and transducers to transform a physical value into an electrical signal. The pre-processing of these signals through electronic circuits - amplification, signal filtering and analogue to digital conversion - are then detailed, in order to provide useful basic information. The second part of the book moves from elementary data to general complex systems. Topics covered include instrumentation and measurement chains, sensor modelling, digital signal processing and diagnostic methods and the concept of smart sensors. A chapter is specifically devoted to microsystem design and applications. Numerous industrial examples are described in this book.
Translated from the French.
Includes bibliographical references and index.
Print version record.
Keywords: Measurement; Engineering instruments; Scientific apparatus and instruments; Detectors; Electronic books